Kumare [videorecording (DVD)] - Gandhi, Vikram (Kino Lorber, Inc., 2013)
"A provocative social experiment-turned-documentary, Kumare follows American filmmaker Vikram Gandhi as he transforms himself into a wise Indian guru, hoping to prove the absurdity of blind faith. Instead, he finds himself forging profound connections with people from all walks of like -- and wondering if and when to reveal his true self...winner of South by Southwest's Audience Award, Kumare is an insightful look at faith and belief."--Case.